(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
Introduction: Patients with chronic stenosis of their ear canal may benefit from additively manufactured individualized drug containing external ear canal implants (EECI) [1] that keep the ear canal open and support the healing of the affected tissue. To guarantee the safety of the patients, the sterilization of implants is important. Autoclaving is a fast and well-established sterilization method, but the heat of the process may damage any drug contained within the implants. To evaluate the suitability of autoclaving EECIs, we tested samples for bio-efficacy and the released drug amount within 3 days. Methods: Three EECIs were 3D printed with an EnvisionTEC Bioplotter (Manufacturer Series, Desktop Metal, Burlington, USA) using UV-Silicone 60A MG (Momentive, Niskayuna, USA) [1] loaded with 1 (w/w) % dexamethasone (DEX, caelo, Hilden, Germany) and 0.3 (w/w) % Ciprofloxacin (Cipro, Sigma Aldrich, Hamburg, Germany). Samples were autoclaved with a Lisa Remote Plus Sterilizer (W&H, Bad Reichenhall, Germany) at a maximum temperature of 134°C for the duration of 350s. Next, the samples were incubated at 37°C for 72 h in isotonic sodium chloride solution (0.9 (w/v) % NaCl, 1 ml NaCl per 0.2 g sample). For the analysis of released drug content within the incubated NaCl, an Ultra High Precision Chromatograph (Xevo Qtof MS, Waters, Germany) coupled with a time-of-flight micro-mass spectrometer (Q-TOF, Waters) was used [2]. The bio-efficacy was assessed using a TNF? (tumor necrose factor-?) reduction assay [1], pure DEX (35,33 µg/ml) served as positive control. Results: 12.94 ± 0.29 µg/ml of DEX and 1.67 ± 0.06 µg/ml Cipro were released from the samples within 72h. The TNF? production was reduced by 80.66 ± 0,02 % (pure DEX) and 58.45 ± 0,10 % (sterilized samples). Conclusion: Since the supernatant of the sterilized samples induce TNF? reduction it can be concluded that an effective amount of DEX survives the autoclaving. The bio-efficacy of the released ciprofloxacin will be evaluated via a zone of inhibition test. Overall, autoclaving may be used to sterilize DEX- containing 3D printed silicone implants. Whether the samples will have a therapeutic effect in the patient will have to be shown by future studies. Author’s statement Conflict of interest: Authors state no conflict of interest. Animal models: Not applicable. Informed consent: Not applicable. Ethical approval: Not applicable. Acknowledgments: We thank M. Kreienmeyer for her help. Research funding: This work was funded by the Graduate School RNApp and the Institute for Biomedical Translation (IBT) Lower Saxony. References [1] Matin-Mann, F.; Gao, Z.; Schwieger, J.; Ulbricht, M.; Domsta, V.; Senekowitsch, S.; Weitschies, W.; Seidlitz, A.; Doll, K.; Stiesch, M.; et al. Individualized, Additively Manufactured Drug-Releasing External Ear Canal Implant for Prevention of Postoperative Restenosis: Development, In Vitro Testing, and Proof of Concept in an Individual Curative Trial. Pharmaceutics 2022, 14, 1242. doi: 10.3390/pharmaceutics14061242 [2] Guo, MF; Zhou, J; Zhang, HH; Zhong, P; Xu, JD; Zhou, SS; Long, F; Zhu, H; Mao, Q; Li, SL. UPLC-QTOF-MS/MS assisted UPLC-TQ-MS/MS strategy to comparatively investigate the rat pharmacokinetics of N-acetyldopamine oligomers derived from Cicadae Periostracum, Journal of Chromatography B 2023, Volume 1226, doi: 10.1016/j.jchromb.2023.123806.